Felbamate in Intractable Childhood Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Of 51 children with intractable seizures treated for two months with add on felbamate (50-75 mg/kg/day) at the Scottish Rite Children's Hospital, Atlanta, GA, 51% responded with improved seizure control, 22% were unchanged, and 28% had increased seizure frequency.